2020
DOI: 10.11646/zootaxa.4852.2.3
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Maraenobiotus (Copepoda, Harpacticoida) from Lena River Delta (North-Eastern Siberia)

Abstract: A new species of harpacticoid copepod of the family Canthocamptidae, Maraenobiotus supermario sp. nov. is described. The new species was found in interstitial waters of the moss tundra of the Lena River Delta, Siberia. This species belongs to the vejdovskyi-species group. The new species differs from its congeners in the apical caudal setae lacking a bulbous proximal part, and in the unique structure of the mandibular palp with only one seta. We also present detailed figures and description of sensilla and por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 739 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The first is a decrease in the number of spinules until their complete disappearance. This is typical condition for one of the groups of spinules on the first segment of the female antennule, in the studied Bryocamptus it is one-two spinules, and for example in Maraenobiotus they are already completely absent ( Novikov and Sharafutdinova 2020 ). The second mechanism is a strong decrease in these spines, also up to complete disappearance.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The first is a decrease in the number of spinules until their complete disappearance. This is typical condition for one of the groups of spinules on the first segment of the female antennule, in the studied Bryocamptus it is one-two spinules, and for example in Maraenobiotus they are already completely absent ( Novikov and Sharafutdinova 2020 ). The second mechanism is a strong decrease in these spines, also up to complete disappearance.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have shown a very low level of knowledge of the freshwater Harpacticoida fauna in the Russian Arctic. Previously, we discovered several new species from the genera Moraria , Bryocamptus , Maraenobiotus , Canthocamptus ( Novikov and Sharafutdinova 2020 ; Novikov et al 2021 ). In this paper, we consider three species of Bryocamptus from the Bryocamptus ( Bryocamptus ) minutus (Claus, 1863) species group with descriptions of two new species from the Arctic.…”
Section: Introductionmentioning
confidence: 99%